Scoping Review: Tren Terbaru dalam Manajemen Sumber Daya Manusia di Era Digital pada Tahun 2012-2022 - Clara Sabrina; Sukrispiyanto (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2023)
Human resource management has undergone significant changes over the past decade with the advancement of technology and the digital era. This scoping review aims to explore the latest trends in human resource management in the period 2012-2022 and their implications for human resource development in 2023. The scoping review method was used to collect and analyse related literature from various sources, including journals, books, and online publications. The results show that human resource management has changed to become more strategic, focus on employee development, and adopt new technologies such as artificial intelligence and data analytics to improve efficiency and effectiveness. Some of the latest trends in human capital management include a focus on employee well-being, work flexibility, diversity and inclusion, and digital skills development. The implication of these trends is that human resource development must adapt to these changes, taking into account the needs and expectations of employees and utilising the new technologies available. This scoping review provides a better understanding of the latest trends in human resource management in the digital era in the period 2012-2022, and provides an outlook on how human resource development can be adapted to these changes in 2023. This can make a positive contribution to organisations in facing future challenges and opportunities.